Realist Evaluation of the Use of Patient Experience Data to Improve the Quality of Inpatient Mental Health Care (EURIPIDES) in England: study protocol. Issue 6 (14th June 2018) - Weich, Scott; Fenton, Sarah-Jane Hannah; Bhui, Kamaldeep; Staniszewska, Sophie; Madan, Jason; Larkin, Michael; Newton, Elizabeth; Crepaz-Keay, David; Canaway, Alastair; Croft, Charlotte; Griffiths, Frances
Abstract : Introduction: Inpatient mental healthcare continues to be an area of high risk and where patients report negative experiences. To ensure the patient voice is heard, National Health Service (NHS) Trusts are required to collect feedback from patients routinely. We do not know what kinds of feedback are most important or what management processes are needed to translate this into effective action plans. Further, we do not know if this makes any difference to the patients themselves. This study seeks to explore which of the many different approaches to collecting and using patient experience data are the most useful for supporting improvements in inpatient mental healthcare. The overarching aim of the study is to arrive at recommendations for best practice in the collection and use of patient experience data in NHS England adult inpatient mental health settings. We present the protocol for Realist Evaluation of the Use of Patient Experience Data to Improve the Quality of Inpatient Mental Health Care study (EURIPIDES). Methods and analysis: The study is composed of five work packages (WPs), including a systematic review of patient experiences (WP1); a telephone survey to assist the selection of case sites (WP2); six indepth case studies involving interviews with service users, carers and staff to enable a realist evaluation of the use of patient experience to improve quality in adult inpatient mental health services (WP3); an economic evaluation of patient experience feedback activity (WP5); and a consensus conference (WP4). We discuss the methodological rationale for the five WPs. Ethics and dissemination: This study has received approval from West Midlands/South Birmingham NHS Research Ethics Committee. The outcome of the consensus conference meeting (WP4) will form the basis of the outputs to be disseminated to NHS providers. Dissemination will also take place through publications and presentations at relevant conferences.